The potential and differences between mulch and organic matter in reducing drought stress in plants – a review - Hidayat Saputra; Mochamad Arief Soleh; Jajang Sauman Hamdani; Andy Saryoko (Cogent Food & Agriculture)
The information on the potency and role of mulch and organic matter in coping with drought is unclear and limited. In this article, we provide a literature review on the types, doses of mulch and organic matter in drought research, and their role in soil properties, and plant resilience. We conclude that using mulches and organic matter can help reduce the impact of drought by improving soil properties. The difference lies in mulch’s ability to minimize evaporation i.e. 28–58.8% and control soil temperature by maintaining an increase at 2–3 °C, thereby enhancing soil moisture up to 4.6–22%. However, information on these impacts is limited to organic matter. Meanwhile, organic matter directly contributes to improving physical properties such as soil structure, aggregation, and aeration, which in turn enhance soil infiltration capacity by 39–44%, increase soil water retention up to 50%, soil water holding capacity, and stimulate better root growth. Mulching and adding organic matter also enhance physiological and crop yields in dry conditions. Plastic mulch has a greater impact in reducing evaporation rates and increasing water use efficiency (WUE) by 12–38.9% higher than organic mulch. Furthermore, the influence of mulch on crop production enhancement is greater than organic matter (19–145% versus 31%) in this review. It is important to note that the effects of different types of mulch, organic matter, and their combinations on plants during drought and different growth stages are not well understood. More research is needed in the future to address these knowledge gaps.